The Practice of Buying and Selling Manure in the View of Islam in Dadapan Village, Solokuro Subdistrict, Lamongan Regency - A'ida Nur Ilmiyah (Universitas Negeri Surabaya, 2025)
The practice of buying and selling in Dadapan Village is often carried out by the local community. This type of research is a field study (field research). The purpose of this research is to find out how the mechanism of buying and selling manure and to find out the legal analysis of buying and selling manure. The objects in this sale and purchase transaction are cow manure, chicken (manure) which are livestock waste which are only thrown away and over time are used as agricultural fertilizer. The practice of buying and selling animal manure that is currently taking place in Dadapan village has implemented good buying and selling practices. Payment for buying and selling transactions can be paid directly or when the goods have arrived. Cow dung is unclean, but the dung has turned into a dry form where in the Islamic view this has become permissible. The law of buying and selling animal dung from an Islamic point of view has been implemented, because in this case some people donate to their closest people or relatives. The practice in this village has not yet implemented the practice of buying and selling in terms of contracts.